Candesartan prevents resiniferatoxin-induced sensory small-fiber neuropathy in mice by promoting angiotensin II-mediated AT2 receptor stimulation. (November 2017) - Bessaguet, Flavien; Danigo, Aurore; Magy, Laurent; Sturtz, Franck; Desmoulière, Alexis; Demiot, Claire
Abstract: Sensory defects associated with small-fiber neuropathy (SFN) can lead to profound disabilities. The relationship between the sensory nervous system and modulation of the renin-angiotensin system (RAS) has been described and focused on pain and neurodegeneration in several animal models. We have recently developed an experimental model of functional sensory neuropathy showing thermal hypoalgesia and neuropeptide depletion without nerve fiber degeneration. Here, we aimed to determine whether the modulation of angiotensin II (Ang II) activity could prevent sensory neuropathy induced by RTX. Control and RTX mice received ramipril, an Ang II converting enzyme (ACE) inhibitor, (0.5 mg/kg/day) or candesartan, an Ang II type 1 receptor (AT1R) blocker (0.5 mg/kg/day), one day before vehicle or RTX administration, and each day for the next seven days. Ramipril did not have a beneficial effect in RTX mice, whereas candesartan prevented thermal hypoalgesia and reduced neuropeptide depletion in intraepidermal nerve fibers and dorsal root ganglion neurons. The preventive effect of candesartan was not observed in mice deficient for the Ang II type 2 receptor (AT2R) and was counteracted in wild type mice by EMA200, an AT2R antagonist (3 mg/kg/day). Thus, candesartan may promote AT2R activation by blocking AT1R and increasing Ang II production and enhance its mechanisms of neuroprotection in our RTX model. Our finding that candesartan prevents nociception deficits and neuropeptide depletion encourages the evaluation of its therapeutic potential in patients presenting SFN, particularly those who experience chemotherapy-induced SFN. Highlights: Decrease Ang II production has no beneficial effect on RTX-induced hypoalgesia. AT1R blockade prevents RTX-induced hypoalgesia and CGRP/SP depletion. AT2R blockade has no beneficial effect on development of RTX-induced hypoalgesia. Effect of candesartan is counteracted by AT2R blocker and in AT2R KO mice. Neuroprotective effects of candesartan is indirectly mediated by AT2R stimulation.